Applying the behavior change wheel to design de-implementation strategies to reduce low-value statin prescription in primary prevention of cardiovascular disease in primary care - Sanchez, Alvaro; Elizondo-Alzola, Usue; Pijoan, Jose I.; Mediavilla, Marta M.; Pablo, Susana; Sainz de Rozas, Rita; Lekue, Itxasne; Gonzalez-Larragan, Susana; Llarena, Marta; Larrañaga, Olatz; Helfrich, Christian D.; Grandes, Gonzalo (Frontiers in Medicine, 2022)
Introduction A substantial proportion of individuals with low cardiovascular risk receive inappropriate statin prescription for primary prevention of cardiovascular disease (CVD) instead of the evidence-based recommendations to promote healthy lifestyle behaviors. This study reports on the structured process performed to design targeted de-implementation strategies to reduce inappropriate prescription of statins and to increase healthy lifestyle promotion in low cardiovascular risk patients in Primary Care (PC). Methods A formative study was conducted based on the Theoretical Domains Framework and the Behavior Change Wheel (BCW). It comprised semi-structured interviews with PC professionals to define the problem in behavioral terms; focus groups with Family Physicians and patients to identify the determinants (barriers and facilitators) of inappropriate statin prescription and of healthy lifestyle promotion practice; mapping of behavioral change interventions operationalized as de-implementation strategies for addressing identified determinants; and consensus techniques for prioritization of strategies based on perceived effectiveness, feasibility and acceptability. Results Identified key determinants of statin prescription and healthy lifestyle promotion were: the lack of time and clinical inertia, external resources, patients' preferences and characteristics, limitation of available clinical tools and guidelines, social pressures, fears about negative consequences of not treating, and lack of skills and training of professionals. Fourteen potential de-implementation strategies were mapped to the identified determinants and the following were prioritized: 1) non-reflective decision assistance strategies based on reminders and decision support tools for helping clinical decision-making; 2) decision information strategies based on the principles of knowledge dissemination (e.g., corporative diffusion of evidence-based Clinical Practice Guidelines and Pathways for CVD primary prevention); 3) reflective decision-making restructuring strategies (i.e., audit and feedback provided along with intention formation interventions). Conclusions This study supports the usefulness of the BCW to guide the design and development of de-implementation strategies targeting the determinants of clinicians' decision-making processes to favor the abandonment of low-value practices and the uptake of those recommended for CVD primary prevention in low-risk patients. Further research to evaluate the feasibility and effectiveness of selected strategies is warranted. Clinical trial registration Sanchez A. De-implementation of Low-value Pharmacological Prescriptions (De-imFAR). ClinicalTrials.gov, Identifier: NCT04022850. Registered July 17, 2019. In: ClinicalTrials.gov. Bethesda (MD): U.S. National Library of Medicine (NLM). Available from: https://www.clinicaltrials.gov/ct2/show/NCT04022850.